Pengaruh Penerapan Strategi Question Students Have (QSH) untuk Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran PAI dan Budi Pekerti di SMPN 3 Bukittinggi - Rodiatud Diniyah; Desti Sartini (YASIN, 2026)
The cognitive learning outcomes of seventh-grade students in Islamic Religious Education and Character Education at SMPN 3 Bukittinggi had not yet met the Learning Objective Achievement Criteria (KKTP) in many cases, indicating the need for a learning strategy capable of encouraging students’ active engagement. This study aimed to analyze the effect of implementing the Question Students Have strategy on the learning outcomes of seventh-grade students in Islamic Religious Education and Character Education. The study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The research sample was selected through purposive sampling, while data were collected using objective tests in the form of a pretest and posttest. The results showed that the mean learning outcome score of the experimental class was 68.00, which was higher than that of the control class at 56.03. The hypothesis test yielded a significance value of 0.006 < 0.05; therefore, H₀ was rejected and Hₐ was accepted. These findings indicate that the implementation of the Question Students Have strategy had a significant effect on students’ learning outcomes. Thus, this strategy can be used as an alternative active learning approach to increase student engagement and support the achievement of learning outcomes in Islamic Religious Education and Character Education.